Policy autonomy, coordination or harmonization in the persistently heterogeneous European Union? - Ludek Kouba; Michal Mádr; Danuše Nerudová; Petr Rozmahel (WWWforEurope, 2015)
The European integration process is ongoing. Europe is still heterogeneous. Within this context, the paper addresses the question of whether policies in the EU should head towards autonomy, coordination or harmonization. Taking the path dependence effect into account, in the papers' opinion, Europe has gone too far in its integration process to be able to continue with policies fully under the competencies of individual member countries. Furthermore, the establishment of the common currency in the EU as a result of deep harmonization in the monetary policy area is an unambiguous precedent with many consequences. First of all, the habitual question still arises in the literature: does fiscal policy need to be harmonized to a comparable level, as these two policies necessarily complement each other? The paper argues that it does not. First, the authors build on the theory of fiscal federalism, which often recommends the strengthening of the stabilization function of public finance; typically in the form of rules and surveillance institutions (e.g., Fiscal Compact, the Six-Pac, European Semester). And on the contrary, they usually refute the intensification of the redistribution function, due to the fact that intergovernmental transfers in contemporary Europe are highly unpopular. Second, Europe is still too heterogeneous and it will continue to be so in the future, simply because of the different cultures, mentalities, traditions, social relations and ways of thinking it harbours. In our context, this means that there are significantly different regimes of welfare states and extents of social policies among European countries, which strongly determine the character of public finance. And third, the tax systems across Europe are also highly divergent, with many different features of continued tax competition. Therefore, a top-down harmonization path towards a full fiscal union is neither politically enforceable, nor economically rational. On the other hand, in order to keep the European integration process viable, it is necessary to reduce behaviour with features of moral hazard and free ride and strengthen joint responsibility for the fiscal development of public finances in the EU. In addition to the discussed matter of joint responsibility and fiscal discipline, the paper points out the open coordination method as an approach towards a sustainable alternative path between a fragmented Europe and a European super state.
Keywords: E63; F15; F42; 330; EU integration; European economic policy; European governance; European Monetary Union; Full employment growth path; Good governance; Policy options